2017
DOI: 10.1093/scan/nsx128
|View full text |Cite
|
Sign up to set email alerts
|

External motivation to avoid prejudice alters neural responses to targets varying in race and status

Abstract: Those who are high in external motivation to respond without prejudice (EMS) tend to focus on non-racial attributes when describing others. This fMRI study examined the neural processing of race and an alternative yet stereotypically relevant attribute (viz., socioeconomic status: SES) as a function of the perceiver’s EMS. Sixty-one White participants privately formed impressions of Black and White faces ascribed with high or low SES. Analyses focused on regions supporting race- and status-based reward/salienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 107 publications
(159 reference statements)
5
41
1
Order By: Relevance
“…Our findings also showed that despite Japanese participants' clear negative implicit as well as explicit evaluations of South Korea (Figure 2), conventional univariate fMRI data analyses failed to find differences in activations in any of the prejudice network between the South Korea vs. Japan blocks. Thus, our results are in line with previous studies that did not find such amygdala activations (Brosch et al, 2013;Gilbert et al, 2012;Golby et al, 2001;Li et al, 2016;Mattan et al, 2018;Phelps et al, 2000;Richeson et al, 2003;Stanley et al, 2012;Terbeck et al, 2015). However, it should be noted that the experimental design of the present study was optimized for individual difference analyses (i.e., acrosssubject correlation).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings also showed that despite Japanese participants' clear negative implicit as well as explicit evaluations of South Korea (Figure 2), conventional univariate fMRI data analyses failed to find differences in activations in any of the prejudice network between the South Korea vs. Japan blocks. Thus, our results are in line with previous studies that did not find such amygdala activations (Brosch et al, 2013;Gilbert et al, 2012;Golby et al, 2001;Li et al, 2016;Mattan et al, 2018;Phelps et al, 2000;Richeson et al, 2003;Stanley et al, 2012;Terbeck et al, 2015). However, it should be noted that the experimental design of the present study was optimized for individual difference analyses (i.e., acrosssubject correlation).…”
Section: Discussionsupporting
confidence: 93%
“…However, past findings are not necessarily consistent, and the amygdala's involvement in negative prejudice toward an outgroup still remains unclear. For example, while some studies found increased amygdala activation in response to racial outgroup faces compared to ingroup faces (Cunningham et al, 2004;Hart et al, 2000;McCutcheon et al, 2018;Wheeler and Fiske, 2005), a number of other studies failed to find such amygdala activations (Brosch et al, 2013;Gilbert et al, 2012;Golby et al, 2001;Li et al, 2016;Mattan et al, 2018;Phelps et al, 2000;Richeson et al, 2003;Stanley et al, 2012;Terbeck et al, 2015). Furthermore, even among those studies that found amygdala activations, its functional interpretations differ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in research investigating the complexity of race by social class stereotypes is emerging as an important future direction of social psychological research (e.g., Brannon et al, 2017;Brannon & Markus, 2013;Kraus, Rucker, et al, 2017;Mattan et al, 2017;Mattan et al, 2018;Richeson & Sommers, 2016). Continued investigation of the effects of race and social class on intergroup processes will supplement the current literature by elaborating on many effects previously attributed to only race or only social class.…”
Section: Codamentioning
confidence: 99%
“…In this review, we advocate for an intersectional approach (i.e., considering how multiple social categories interact simultaneously) to race and social class by examining how race and social class intersect to influence a variety of intergroup processes including stereotypes, attitudes, cognition, and behaviors. We build this review upon recent calls for and renewed interest in understanding the intersection between race and social class for intergroup processes (e.g., Brannon, Higginbotham, & Henderson, 2017;Brannon & Markus, 2013;Kraus, Rucker, et al, 2017;Mattan, Kubota, & Cloutier, 2017;Mattan, Kubota, Dang, & Cloutier, 2018;Richeson & Sommers, 2016).…”
mentioning
confidence: 99%